Study on Kaishochi changes before and after the war-damage-recovery land readjustment programs of Nagoya City, Japanese Castle Town - Matsuura, Kenjiro (International Planning History Society Proceedings, 2018)
In this paper, focusing on open temple-type kaishochi (open areas ensconced in the design of urban blocks) located in the district of Nagoya City in Japan’s Aichi Prefecture, we will review the effects of the war-damage-recovery land readjustment programs, through which the city has experienced a number of major transformation. Specifically, we will elucidate the actual state of such kaishochi before and after the project by examining residual trends of temple-type structures by using maps produced before and after the project implementation. Targeting 66 Edo-period kaishochi blocks in the Nagoya Castle district, we first analyzed the differences between the land usage decrease rate for the whole district and that for the targeted kaishochis. Next, we analyzed transformations of usage and form using the maps produced before and after the project implementation. As a result of our analysis, the following three points were clarified. First, even though the number of temple-type kaishochis is decreasing, there has been little change in the area they occupy. Second, there has been little change in kaishochi usage before and after the project implementation. Third, looking at the kaishochi forms, we can find changes from Flagpole type (large inner area with narrow outside access), no-contact type (large inner area with no public access to outside roads), and integrated type (large access to outside road).